2022
DOI: 10.1021/acs.jpcb.2c06630
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Analysis of Physical and Chemical CO2 Absorption by Tri- and Tetraepoxidized Imidazolium Ionic Liquids

Abstract: The efficient capture of CO 2 from flue gas or directly from the atmosphere is a key subject to mitigate global warming, with several chemical and physical absorption methods previously reported. Through polarizable molecular dynamics (MD) simulations and high-level quantum chemical (QC) calculations, the physical and chemical absorption of CO 2 by ionic liquids based on imidazolium cations bearing oxirane groups was investigated. The ability of the imidazolium group to absorb CO 2 was found to be prevalent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Recently, in addition to the previously studied two-site epoxyimidazolium complexes, tri-and tetraepoxyimidazolium compounds have also been synthesized and characterized to give additional epoxy sites to IL−epoxy monomers. 30,38 In this study, it was found that these monomers can give varied results when compared to the standard two-site epoxy IL previously synthesized. In this study, simulations were performed to assess the local domains of the amine−epoxy solution before any polymerization takes place.…”
Section: ■ Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Recently, in addition to the previously studied two-site epoxyimidazolium complexes, tri-and tetraepoxyimidazolium compounds have also been synthesized and characterized to give additional epoxy sites to IL−epoxy monomers. 30,38 In this study, it was found that these monomers can give varied results when compared to the standard two-site epoxy IL previously synthesized. In this study, simulations were performed to assess the local domains of the amine−epoxy solution before any polymerization takes place.…”
Section: ■ Introductionmentioning
confidence: 88%
“…These IL epoxy/amine polymers were found to have a high thermal stability of over 300 °C in addition to a high ionic conductivity and storage modulus, making them ideal for applications as robust polymers capable of retaining and remembering shape. Recently, in addition to the previously studied two-site epoxyimidazolium complexes, tri- and tetraepoxyimidazolium compounds have also been synthesized and characterized to give additional epoxy sites to IL–epoxy monomers. , In this study, it was found that these monomers can give varied results when compared to the standard two-site epoxy IL previously synthesized. In this study, simulations were performed to assess the local domains of the amine–epoxy solution before any polymerization takes place.…”
Section: Introductionmentioning
confidence: 95%
“…In addition, ILs may also offer several advantages, such as low volatility and higher thermal stability, and lower solid-solid migration compared to molecular plasticizers [13]. Moreover, they are also emerging as a new class of 'green plasticizers' and they are an alternative to existing environmentally friendly materials [10,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in previous studies used to determine physical interaction and aggregation, molecular dynamics (MD) and specifically polarizable MD is a more appropriate tool for insight into the modes of interaction between such entities. [19,20] These can be specifically helpful in the instance where the probability of π-π stacking is to be analyzed, [21] or the presence of large aggregates are to be determined. [22,23] For a radical ion photocatalyst to be effective, it needs initially to form an assembly with the substrate that is either favorable (exergonic) or "accessibly endergonic" in solution at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…However, the costly nature of QC calculations employing high‐level DFT restricts the observation of systems on a large enough scale to probe the probability of interaction between substrate and catalyst in a dynamic, multicomponent system. As discussed in previous studies used to determine physical interaction and aggregation, molecular dynamics (MD) and specifically polarizable MD is a more appropriate tool for insight into the modes of interaction between such entities [19,20] . These can be specifically helpful in the instance where the probability of π ‐ π stacking is to be analyzed, [21] or the presence of large aggregates are to be determined [22,23] .…”
Section: Introductionmentioning
confidence: 99%